Analisis Efektivitas Teknik Tendangan Dollyo Chagi Melalui Metode Latihan Beban Kaki Terhadap Kecepatan Dan Akurasi Di Dojang TMC - Charmila Tandi Rerung (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aims to analyze the effectiveness of leg weight training methods on improving speed and accuracy of dollyo chagi kicks in TMC Taekwondo Mountain Child athletes. This research used a quasi-experimental design with pre-test and post-test control group design involving 20 taekwondo athletes divided into experimental group (n=10) and control group (n=10). The experimental group received leg weight training combined with conventional training for 8 weeks, while the control group only received conventional training. Speed was measured using photoelectric timing gates and accuracy using target scoring system. Data analysis used paired t-test and independent t-test with significance level α=0.05. Results showed significant improvement in experimental group for kick speed (12.3% improvement, p=0.003) and accuracy (15.7% improvement, p=0.002) compared to control group which only showed 2.5% and 4.2% improvement respectively. Comparison between groups showed significant differences (p<0.05) with experimental group being superior. Leg weight training method is effective for improving speed and accuracy of dollyo chagi kicks in TMC Mountain Child taekwondo athletes.